Improving Patient Knowledge About Tangibles That Influence Satisfaction in Inpatient Rooms - chichi hafifa transyah; Reni Trevia; Ira Sri Budiarti (Jurnal Abdimas Saintika, 2026)
Patient satisfaction is an important indicator in assessing the quality of hospital services. One of the factors that influence the level of patient satisfaction is tangibles, namely real aspects that can be seen and felt by patients such as cleanliness, comfort of the room, completeness of facilities, and the appearance of health workers. The purpose of Community Service is to increase patient knowledge about tangibles that affect satisfaction in the inpatient room. The method used is counseling, discussion and distribution of leaflets to patients in the inpatient room of Rasuna Said Hospital Tk III Dr. Reksodiwiryo Padang on March 2, 2026. Before the counseling and discussion, patients first filled out a questionnaire to determine the level of patient understanding of tangibles that affect satisfaction, and after the counseling, the same questionnaire was given again to see patient knowledge after the counseling, The number of participants was 16 patients in the inpatient room. The results of the Community Service showed an increase in patient knowledge of more than 90%. The conclusion is that with this counseling and discussion activity, it can increase patient knowledge about tangibles in the inpatient room. It is recommended that the hospital improve the provision of information by providing counseling to increase patient satisfaction in the inpatient ward.